The Validity of Teaching Materials Using the Problem-Based Learning Model of Independent Curriculum Social Sciences Materials in Mobility Elementary Schools - Diana Gusti Alfiyanti; Yeni Erita (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This research is a development carried out to produce a product in the form of a teaching material model with the PBL model of IPS content independent curriculum for students in elementary school. Based on the theoretical studies and field studies carried out, initially a draft teaching material package model was produced with the PBL model of independent curriculum IPS content, which contains identification of SK and KD, identification of indicators, identification of learning objectives. Furthermore, the teaching materials are reflected and revised according to user needs and expert input to obtain the final product. This development is carried out based on the plomp model which emphasizes the needs of users according to the context (teachers and students), meaning that the packages and development models are developed collaboratively (active user involvement) in selected environments. Products are revised based on authentic process data according to user needs (process/formative evaluation), expert tests and small group tests are carried out to perfect the product (summative evaluation). The results of the validation of model teaching materials with the PBL model of independent curriculum IPS content show that the developed teaching materials have been declared valid with an average of 3.75 reaching a percentage of 93.75% with a very valid category, declared practical and effective.